Enablers and barriers for implementing a COS for pulmonary rehabilitation in people with COPD: health professionals’ perspectives - Miranda, Sara (2019)
Patients with chronic obstructive pulmonary disease (COPD) have limited access to pulmonary rehabilitation (PR) despite being a fundamental intervention for their management. Potential of improvement has been used for prioritization; however the response to PR depends on the outcomes used to assess these patients. Currently, there is no core outcome set (COS) for PR. Health professionals are key-stakeholders with an important role on selecting outcomes and implementing PR. However, their views on the enablers/barriers to achieve a successful COS have never been explored. Thus, this study explored health professionals’ views on the potential enablers/barriers for implementing a COS for PR in patients with COPD. Semi-structured interviews were conducted with 10 health professionals (two medical doctors, six physiotherapists, and two nurses, n = 2 20% male, 40.7 ± 14.3 years old, 6.7 ± 9.7 years of experience). Data were analyzed with thematic analysis. Three themes were interpreted. A COS should be: (1) quick, simple, and meaningful; (2) credible and reliable; and (3) free and global. Perceived enablers were having a COS easy to understand by patients and health professionals, which translates the results “that you can see” and is adjustable to each patient; that received inputs from patients’ organizations and recognized societies from different countries to ensure credibility, is available to all community through platforms and social media, and is composed by instruments with strong clinimetric properties. Potential barriers were having a long list of outcomes with time-consuming instruments, outcomes only pertinent for specific contexts, and having charges related to the COS, namely with instruments. However, health professionals felt that overcoming those barriers would allow comparing different programs and grow the investment in effective PR. Although this COS was perceived as challenging by health professionals, it was also recognized as a crucial step to improve the quality of care and change national and international policies regarding PR.